Exercise training (ET) in adult and elderly patients receiving anti-lymphoma treatments is feasible and may improve the provision of care. Issue 3 (23rd February 2021) - Cox, Maria Christina; Nusca, Sveva Maria; Di Landro, Francesca; Marsilli, Gabriella; Stella, Giulia; Sigona, Matilde; Ponzelli, Federica; Passerini Desideri, Jasmine; Di Gregorio, Francesca; Santoboni, Flavia; Vetrano, Mario; Trischitta, Donatella; et al.
Abstract: Lymphoma treatments can produce adverse effects leading to a reduced quality-of-life (QoL). Besides, in patients ≥65years, it can promote an accelerated geriatric decay. We conducted a prospective study on supervised Exercise-Training (ET), in consecutive, patients aged 18–80years, during anti-lymphoma treatments.16/30 (53%), median-age = 65.5y, participated to the ET sessions, this was the Interventional Group (IG); 14/30 (47%), median-age = 63y, were the Reference Group (RG). Both groups participated to the fitness and the QoL assessments, at baseline (T0), 3-months (T1) and 6-months (T2) after the start of chemotherapy. The adherence to the ET program was 50% (95% CI:36–64%). The IG showed substantial improvements compared to the CG in cardiorespiratory fitness (Cooper test) at both T1 and T2 and in all the functional domain of the QoL questionnaire (QLQ-C30) at T2. This study showed ET, during chemotherapy, is feasible and safe, even in patients ≥65 years. Furthermore, it may improve the provision of care.